Video viewing as a mediation of learning content-based vocabulary: Assisting students in understanding disciplinary vocabulary in context - Yanto, Elih Sutisna; Nugraha, Sidik Indra (Universitas Pendidikan Indonesia, 2018)
Although much research in the area of second language (L2) vocabulary development has extensively been researched, video text viewing as a strategy for understanding disciplinary vocabulary in context is rarely reported in the literature. To fill this void, the present action research reports the findings of vocabulary self-collection strategy (VSS) along with the use of video as a multi-semiotic medium of understanding disciplinary vocabulary in content-based EFL instruction. Informed by students’ reflective journal, observation, and interview data, students recounted that the VSS encouraged them to learn disciplinary vocabulary in different discourse contexts. Through role scaffolding by a teacher and peer support, they were engaged in the discovery of vocabulary by documenting unfamiliar or interesting words from their readings and by exploring different meanings of vocabulary using e-dictionaries and corpora. The other research findings showed that the students had enhanced their awareness of word classes, word orders, and word meanings. This empirical evidence suggests that VSS can be a catalyst for engaging students in such post-listening tasks as writing a summary of the video text and creating new vocabulary mapping or profiling.